The Effect of Work Environment, Group Development, Leadership, Membership, and Group Cohesiveness on Employees’ Performance of Basic Education Office in Central Jakarta - Istaryatiningtias,; Handayani, Trisni; Yatri, Ika (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this research is to find out the effect of the work environment, group development, leadership, membership, and group cohesiveness on employees’ performance of the Basic Education Office in Central Jakarta. This research was conducted at the Basic Education Office of Central Jakarta. The data had been analyzed using path analysis. The samples of this research were 65 employees of the Basic Education Office in Central Jakarta that selected randomly. The research findings are as follows: (1) there is a direct effect of work environment on group cohesiveness; (2) there is a direct effect of group development on group cohesiveness; (3) there is a direct effect of group on group cohesiveness; (4) there is a direct effect of membership on group cohesiveness; and (5) there is a direct effect of group cohesiveness on employees’ performance. And there are indirect effects of the work environment, group development, leadership, and membership on employees’ performance. Based on those findings, it can be concluded that the variation of employees’ performance is affected directly by variation of group cohesiveness, meanwhile, the group cohesiveness is addicted directly by the work environment, group development, leadership, and membership. Therefore, group cohesiveness should be put into consideration in determining employees’ performance of the Basic Education Office in Central Jakarta.